Kafālah Perspektif Tafsir dan Hadis Aḥkām: Analisis Normatif dalam Fikih Muamalah Kontemporer - Muhibbussabry; Jamil, M.; Yuslem, Nawir (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Kafālah is a guarantee contract in muamalah fiqh that serves to maintain legal certainty and protect rights in transactions, while also reflecting social responsibility and economic solidarity. In contemporary Islamic finance practices, the application of kafālah often emphasizes technical and operational aspects rather than strengthening its normative foundations, thus giving rise to the need for comprehensive normative studies. This article analyzes the concept of kafālah through an integrative approach of tafsir and hadith aḥkām, and affirms its position in fiqh muamalah as a tawthīqī contract. This study uses a normative-qualitative method with an approach of tafsir aḥkām, takhrij and analysis of hadith aḥkām, as well as a study of istinbāṭ law by classical and contemporary fuqaha. The results of the study show that kafālah has strong shar‘i legitimacy in the Qur'an and Sunnah, and is consistently constructed as an accessory guarantee contract without removing the liability of the principal debtor. From the perspective of maqāṣid al-syarī‘ah, kafālah generally falls within the realm of ḥājiyyāt, but in certain contexts it can rise to the level of ḍarūriyyāt. This study strengthens the normative framework of kafālah and provides a conceptual basis for the development of sharia guarantee instruments that are fair and oriented towards public interest.